Microstructural and morphological investigations on Mg-Nb2O5-CNT nanocomposites processed by high-pressure torsion for hydrogen storage applications. (13th March 2020) - Gajdics, Marcell; Spassov, Tony; Kis, Viktória Kovács; Schafler, Erhard; Révész, Ádám
Abstract: A combined deformation process of high energy ball milling and subsequent high-pressure torsion method was applied to synthesize nanocrystalline magnesium powders catalyzed by Nb2 O5 and/or multiwall carbon nanotubes. The effect of the different additives on the kinetics of the milled powders and the bulk disks produced by simultaneous uniaxial compression and severe shear deformation was examined in a Sieverts'-type apparatus. The microstructure and the morphology of the as-processed samples and the additives were characterized by X-ray diffraction and high-resolution transmission electron microscopy, respectively. Microstructural changes and morphological alterations after several absorption-desorption cycles were also studied. It was found that high-pressure torsion has significantly changed the texture of magnesium and the shape of carbon nanotubes. The combined use of Nb2 O5 and carbon nanotubes was found to improve the desorption kinetics of Mg. Influence of the additives and processing methods on the evolution of the microstructure will also be demonstrated. Highlights: HEBM and HPT deformation were applied on Mg powders catalyzed by Nb2 O5 and CNT. Remarkable (002) texture develops after the torsion process for all compositions. Nb2 O5 is required to achieve appropriate hydrogen sorption properties (6.5 wt%). Either the combination of HEBM + HPT or the addition of CNT catalyst is required. A synergetic effect takes place between the Nb2 O5 and CNT additives.